SCHOOLS OF STRATEGIC PLANNING: A CRITICAL ANALYSIS OF EXISTING CONCEPTS - Togayev, Salim Sobirovich; Abdumalikov, Raxmatullo Sherzodbek o‘g‘li (Educational Research in Universal Sciences, 2023)
The article considers the essence of the concepts proposed by various schools of strategic management. Based on a logical analysis of methodological approaches to strategic management, the main problems of these schools are identified.